Sensory system for the electronic water meter - Garmabdari, Rasoul; Shafie, Suhaidi; Mohd Isa, Maryam
Currently, energy management has become one of the most controversial issues in the world due to limitations in natural resources, and the measurement of water consumption by means of water meter. Measuring water consumption has been considered a serious matter in order to control and manage the resources of water. Therefore, there are many approaches, which have been offered such as Ultrasonic, Electromagnetic, and Mechanical mechanism. However, there have been a lot of restrictions in them such as providing the power supply for the meter, the cost of implementation, accuracy of measurement etc. The circuit was designed based on the Hall-Effect sensor by applying a new technique to remove the effects of disturbing signals, which might be derived either of a strong electromagnetic field or temperature. Furthermore, this proposed technique will reduce the number of applied sensors. The CMOS technology was employed to reduce the power consumption, the effects of input resistance on sensor and, etc. The output of each sensor’s signal is going to be shown as following, which illustrates the system performance. consequently, the electronic water meter has been designed to be not affected by electromagnetic field, temperature and so on, furthermore the reduction power consumption and the its cost was considered to be mass produced in the design.